In-Bore Dynamic Measurement and Mechanism Analysis of Multi-Physics Environment for Electromagnetic Railguns - Yuxin Yang; Keren Dai; Qiang Yin; Peng Liu; Da Yu; Haojie Li; He Zhang (IEEE Access, 2021)
Electromagnetic launch technology has important applications in many fields. However, the extremely harsh multi-physics environment during the launch is quite different from that of conventional guns. Little experimental research studied the dynamic distribution of the extreme impact environment and magnetic fields in the projectile. To this end, this paper designs a projectile-borne storage testing system for the dynamic measurement of harsh multi-physics environments. The detailed assessment of the measured dynamic multi-physics field shows that the velocity skin effect (VSE) is an important factor affecting the dynamic results. It causes a higher current density in the armature, and the magnetic induction and acceleration in the dynamic experiment are lower than those in the static-based experiment and simulation. Moreover, it causes the concentrated heat on the trailing edge of the armature, which lead to the melt-wave erosion, even affects the movement of integrated projectile during launch. Furthermore, the physical mechanism behind these phenomenon is revealed, and the causes of muzzle velocity error are analyzed. In conclusion, a feasible, dynamic measurement method for multi-physics coupled environments is presented, which can provide references for follow-up modeling and simulation researches and promote the development of railguns.